2018
DOI: 10.1158/1078-0432.ccr-17-2709
|View full text |Cite
|
Sign up to set email alerts
|

p53-Reactive T Cells Are Associated with Clinical Benefit in Patients with Platinum-Resistant Epithelial Ovarian Cancer After Treatment with a p53 Vaccine and Gemcitabine Chemotherapy

Abstract: there were no DLTs, but 3 of 11 patients came off study early due to gemcitabine-attributed adverse events (AE). Minimal AEs were attributed to p53MVA vaccination. Immunologic and clinical response: enhanced recognition of p53 peptides was detectable after immunization in both the CD4 and CD8 T-cell compartments in 5 of 11 and 6 of 11 patients, respectively. Changes in peripheral T regulatory cells (Tregs) and myeloid-derived suppressor cells (MDSC) did not correlate significantly with vaccine response or prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Several groups have already shown endogenous T cell reactivity across OvCa patients to various TAA such as mesothelin [47], wild-type or mutated p53 [48][49][50], NY-ESO-1 [51], and Her2/neu [52] among others. However, therapies targeting a particular TAA, either through peptide vaccine or chimeric antigen receptor T cells, have had mixed results due to loss of the target antigen [51] or poor persistence [53] for example.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have already shown endogenous T cell reactivity across OvCa patients to various TAA such as mesothelin [47], wild-type or mutated p53 [48][49][50], NY-ESO-1 [51], and Her2/neu [52] among others. However, therapies targeting a particular TAA, either through peptide vaccine or chimeric antigen receptor T cells, have had mixed results due to loss of the target antigen [51] or poor persistence [53] for example.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of this vaccine in advanced CRC or small cell lung carcinoma patients did not show benefit, despite inducing a p53-specific T cell response (Antonia et al, 2006;Chiappori et al, 2019;van der Burg et al, 2002). However, one phase I trial using MVAp53 gene therapy in platinum-resistant ovarian cancers showed an increase in patient survival (Hardwick et al, 2018). The potential to combine this approach with checkpoint inhibitors remains to be explored.…”
Section: P53 Accumulation In Cancer Increases Circulating B Cell Automentioning
confidence: 99%
“…This circumvents the inhibition of activated, proliferating vaccine-induced T cells, and can dramatically foster T-cell responses by depletion of unwanted myeloid cells [133]. Gemcitabine has been explored in mice and humans in combination DC and other cancer vaccines with promising results [137][138][139][140][141]. Reassuringly, gemcitabine also synergizes with two other types of immune therapy, namely oncolytic virotherapy and ICB [142][143][144].…”
Section: Challenges and Future Perspectives Of DC Vaccine Therapymentioning
confidence: 99%